Portal Vein Thrombosis in Polycythaemia Vera: A Case Report - Kabir, Amin Lutful; Khatun, Hazera; Rahman, Farzana; Habib, Ahsan; Rahman, Hafizur; Ur Rahaman, Mohammad Ferdous (Medicine Today, 2012)
Portal vein thrombosis, commonly associated with cirrhosis of liver and thrombophilia, is one of the rare causes of sudden severe abdominal pain. In the absence of noncirrhotic non-malignant extra hepatic portal vein thrombosis (EPVT), myeloproliferative disease (MPD) should always be considered. We describe a case of Polycythaemia Vera (PV) presenting with severe abdominal pain due to portal vein thrombosis. The patient was prescribed life-long warfarin, beta adrenergic blocker and aspirin. Due to uncontrolled platelet and white blood cell count he was later prescribed cytoreductive therapy. Medicine Today 2010 Volume 22 Number 02 Page 99-102 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12444